Tuberculosis management and referral practices among traditional medicine practitioners in Lagos, Nigeria - Victor A. Adepoju; Olanrewaju Oladimeji; Maureen N. Sibiya; Jude Inegbeboh; Ginika Egesemba (AOSIS, 2023)
Introduction: Despite the potential role of Traditional Birth Attendants (TBAs) and Traditional Healers (THs), little is known about their knowledge of tuberculosis (TB) management and referral practices in Nigeria. Objective: To determine knowledge and self-reported practices of traditional birth attendants and traditional healers in managing TB in Lagos, Nigeria. Methods: A cross-sectional study of 120 THs and TBAs in three high TB burden Local Government Areas (LGAs) in Lagos, Nigeria. Data were collected between April 2018 to September 2018 through interviewer-administered questionnaires. We used Statistical Package for Social Sciences software for data analyses. Independent predictors of being TBA or TH were determined using logistic regression at the statistical significance of P0.05 and 95% confidence interval. Results: TB knowledge increased from 52.7% pre-test to 61.7% post-test and did not differ between TBAs and THs. Of the 120 Traditional Medical Practitioners studied, 70% (84) never treated TB; 57.3 % (69) ever referred chronic cough patients to a health facility; 90% (108) were willing to collaborate with National Tuberculosis, Leprosy and Buruli Ulcer Control Programme (NTBLCP), 85% (102) attached monetary and token incentive as a condition for the collaboration. THs had decreased odds of ever referring TB patient to the hospital (AOR: 0.3, 95% CI:0.14-0.64, P=0.002); currently referring TB patients (AOR: 0.06, 95% CI:0.02-0.17, P0.0001) and consulting 40 patients in a year (AOR: 0.22,95% CI:0.09-0.53, P0.0001). Conclusion: Majority of the THs and TBAs were willing to collaborate with NTBLCP in the identification and referral of Presumptive TB patients. We suggest that NTBLCP empowers the TBAs and THs to help with an early referral of TB patients.